Integrating reason and intuition: An integrative approach to objectivizing subtle cues - Nandram S.S.; Mourmant G.; Bindlish P.K.; Sandra D. (My University, 2025)
This chapter shows that decision-making involves interactions between reason and intuition. It explains how several subtle cues, when integrated, lead to a holistic, coherent understanding of what happens when decision makers act in a context that is not conditioned but creates room for natural stimuli. The emergence of subtle cues influenced by internal enablers can be trained by the organization, but these cues may need a long period of time to have an impact and they may be dependent on individual factors, such as personalities, attitudes, worldviews, and background. The term intuition is derived from the Latin intueri, which means “to look upon.” There are various strategies to cope with the subtle cues. A person may be triggered by earlier cues which may be stored somewhere in the memory and which may lead to new cues. The concept of multilevel, dynamic, holistic perception can be described as two concentric circles in an iterative, dynamic interaction process. © 2020 by Taylor & Francis Group, LLC.